Cervantes entre la realidad y la ficción de su propia obra (Una meditación personal en torno al capítulo 30 de la Segunda Parte). - Pérez, Miguel José; Enciso Orellana, J. (Didáctica. Lengua y Literatura, 1999)
In this chapter of Don Quixote the union between reality and fiction achieved by Cervantes throughout the novel clearly appears. From the beginning, he takes care of the features of credibility of the fiction lived by Don Quixote and Sancho. He wants to write good literature and, with tllat purpose, the novel must comply with reality. Don Quixote asks Sansón Carrasco if it is true that a story about his 111 Miguel josé Pérez Cervantes entre la realidad y la ficción de su propia obra Julia Enciso Orellana deeds has been published; and he himself, as well as Sancho, take great care of knowing whether this printed story complies with truth. We feel as if diese characters were, simultaneously, real and fictional; that is why they reached such renown aud such fame that «there is no nation or language into which they wiU not be transíated». The deep truth depicted by Cervantes benefited the fame and good name of the Ingenioso Caballero de la Mancha.